Implementasi Pembelajaran Berdiferensiasi pada Kurikulum Merdeka Tingkat Sekolah Menengah Atas : Studi Literature Review : Penelitian - Nita Anggraini; Syamsurizal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article examines the implementation of differentiated instruction within the framework of the Merdeka Curriculum in the Biology subject at the Senior High School (SMA) level, using a literature review approach with the PRISMA method. The synthesis of ten scholarly articles analyzed indicates that differentiated instruction has a positive impact on student learning outcomes, engagement, and the development of 21st-century skills. However, its implementation faces challenges such as time constraints, limited teacher capacity, and insufficient policy support. Effective strategies identified include continuous teacher training, teacher collaboration, and the integration of technology and active learning models such as Problem-Based Learning (PBL) and Discovery Learning. This study emphasizes the need for an adaptive, flexible, and inclusive approach to ensure the optimal implementation of differentiated instruction. As a contribution, this research helps develop instructional practices that are more responsive to student diversity and supports national education transformation. Differentiated instruction is also expected to address challenges in the implementation of the Merdeka Curriculum, especially in the Biology subject, by providing opportunities for teachers to design strategies that align with the unique characteristics of each student.